Relationship between spinocranial angle and clinical outcomes after laminoplasty in patients with ossification of the posterior longitudinal ligament - Liu, Zhen; Wang, Zheng; Zhang, Peng; Lin, Wei; Liu, De-Feng; Zhou, Xin; Zheng, Ji-Hui (Frontiers in Surgery, 2022)
Background: The aims of this study were to identify the relationship between the spinocranial angle (SCA) and clinical outcomes and to explore whether the SCA is a suitable indicator to predict clinical outcomes for patients with ossification of the posterior longitudinal ligament (OPLL). Methods: Sixty-five patients with cervical OPLL who underwent laminoplasty with at least 24 months of follow-up were selected for the current study and were divided into two groups according to whether the SCA was greater than or less than the mean preoperative SCA. Sagittal alignment changes were compared between the groups. The Pearson correlation coefficient was applied to assess the relationship among sagittal parameters. Univariate and multiple linear regression analyses were applied to identify the relationship between the recovery rate (RR) and radiological parameters. Results: Patients were classified into two groups based on the mean value of preoperative SCA (85.1°). SCA was negatively correlated with T1 slope (T1s) and cervical lordosis (CL) and positively correlated with the C2–7 sagittal vertical axis (cSVA) (p < 0.001). Patients with lower SCA had larger T1s and CL preoperatively and at the follow-up (T1s: p < 0.001; CL: p < 0.001) and showed greater loss of cervical lordosis after laminoplasty (p < 0.001). However, no significant differences in the incidence of kyphosis, Japanese Orthopaedic Association (JOA) or RR were noted between the two groups. Although Pre-SCA, Pre-CL, F/U-CL and Pre-T1sCL were significantly associated with RR, these indicators were not associated with RR in the multivariate regression analysis. Conclusions: Patients with lower SCA tended to have higher T1s and CL before surgery and greater loss of cervical lordosis at the follow-up visit but still maintained a greater lordosis angle. Although preoperative SCA is significantly related to RR, the relationship is not sufficient to indicate that preoperative SCA can be used to predict clinical outcomes. Therefore, further research is needed to confirm the impact of SCA on clinical outcomes for OPLL.